2020
DOI: 10.1024/0301-1526/a000860
|View full text |Cite
|
Sign up to set email alerts
|

Normative and pathological values of hemodynamic and Doppler ultrasound arterial findings in children

Abstract: Summary. Doppler ultrasound is an effective, useful and remarkably powerful tool in pediatric imaging. If possible, its use is always favored to avoid exposure to radiation or sedatives. By waveform spectrum analysis, Doppler ultrasound reveals information on blood flow and details on normal physiology and pathological processes undiscernible from gray-scale imaging alone. However, Doppler ultrasound remains underused, largely due to the difficult interpretation of changes in Doppler waveforms during childhood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 67 publications
6
3
0
Order By: Relevance
“…CCA RI reached a maximum approximately at 15-20 years and then it fell to values even lower than the observed in childhood. The above described agrees with previous works in children, adolescents, and young or middle-aged adults (Zbornikova and Lassvik, 1986;Scheel et al, 2000;Trihan et al, 2020) (Figures 7C,D).…”
Section: Carotid and Vertebral Arteries Ri And Pisupporting
confidence: 93%
See 4 more Smart Citations
“…CCA RI reached a maximum approximately at 15-20 years and then it fell to values even lower than the observed in childhood. The above described agrees with previous works in children, adolescents, and young or middle-aged adults (Zbornikova and Lassvik, 1986;Scheel et al, 2000;Trihan et al, 2020) (Figures 7C,D).…”
Section: Carotid and Vertebral Arteries Ri And Pisupporting
confidence: 93%
“…Data obtained for ICA RI and PI (Figures 8C,D) agree with previous results (Trihan et al, 2020). Like us, other authors reported an age-related reduction in ICA RI and PI (Yazici et al, 2005;Trihan et al, 2020).…”
Section: Carotid and Vertebral Arteries Ri And Pisupporting
confidence: 91%
See 3 more Smart Citations